2019
DOI: 10.1186/s13012-019-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

Specifying and comparing implementation strategies across seven large implementation interventions: a practical application of theory

Abstract: BackgroundThe use of implementation strategies is an active and purposive approach to translate research findings into routine clinical care. The Expert Recommendations for Implementing Change (ERIC) identified and defined discrete implementation strategies, and Proctor and colleagues have made recommendations for specifying operationalization of each strategy. We use empirical data to test how the ERIC taxonomy applies to a large dissemination and implementation initiative aimed at taking cardiac prevention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 29 publications
(45 reference statements)
3
142
0
Order By: Relevance
“…The Expert Recommendations for Implementing Change (ERIC) project created a taxonomy of discrete implementation strategies, one of which is facilitation [51]. Perry et al [54] tested the ERIC taxonomy in multiple large studies that applied practice facilitation, "a more specific type of implementation facilitation," to support implementation of evidence-based cardiovascular preventive care, and they further refined the ERIC taxonomy. The study found that facilitators did incorporate many other strategies into their efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The Expert Recommendations for Implementing Change (ERIC) project created a taxonomy of discrete implementation strategies, one of which is facilitation [51]. Perry et al [54] tested the ERIC taxonomy in multiple large studies that applied practice facilitation, "a more specific type of implementation facilitation," to support implementation of evidence-based cardiovascular preventive care, and they further refined the ERIC taxonomy. The study found that facilitators did incorporate many other strategies into their efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case in relation to the strategy of building community connections and promoting patient involvement as part of implementation for SMS interventions. In terms of the intervention discussed here, the expected implementation outcomes for strategies included, establishing improved community connections and improved referrals to accessible patient resources [ 31 ]. What the study here shows is that in the instance of the original implementation strategy having to be abandoned, or the strategy not materialising as originally envisaged, making an intervention implementable emerges from network resilience and contingencies which arise as a result of attempts to make the intervention workable on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…While the evidence on effective implementation strategies is growing, much remains unknown about how best to select and enact these strategies for a given context. Currently, such planning usually focuses on which implementation strategies to use, typically informed by knowledge of/hypotheses about likely implementation barriers [1,3,[9][10][11][12][13][14][15], existing evidence about the effectiveness of the strategies [1,3,9,[13][14][15][16], the experience of the implementation team [17], guidance from conceptual models [6,[18][19][20][21][22][23][24][25], and pragmatic concerns [1,3,9,15] including available resources [4,5,13,26]. However, these sources generally do not provide detailed guidance on how these strategies should be operationalized to maximize their impact.…”
mentioning
confidence: 99%